Meta Analisi Pengaruh Model Pembelajaran Numbered Head Together Terhadap Hasil Belajar Matematika Siswa Kelas V SD - Susanto, Florentinus (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to analyze the influence of the Numbered Head Together (NHT) learning model in improving elementary mathematics learning outcomes. The method used in this study is a meta-analysis method. This research begins with formulating a research topic, then from that research topic it is developed again into a research problem formulation, and at the final stage is tracing relevant articles for data collection. The data collection technique in this study is by searching for articles contained in online journals that have been indexed in Google Scholar, and. From the results of further searches, 10 articles were then taken published in online journals that will be used as the basis for this research with the search keywords "Numbered Heads Together (NHT)", "mathematical learning outcomes", and "Mathematics Learning for Grade V Elementary School". Based on the results of the analysis, it turns out that the Numbered Head Together Model can improve student learning outcomes, from the previous 49.91%, to 64.24%.